THER-22. BROMODOMAIN INHIBITORS INDUCE DOWNREGULATION OF DNA DAMAGE REPAIR PATHWAYS AND OFFER NOVEL SYNERGISTIC COMBINATIONS WITH ENHANCED SAFETY PROFILES FOR THE TREATMENT OF MEDULLOBLASTOMA AND GLIOBLASTOMA. (23rd April 2019) - Lam, Fred C; Vu-Han, Tu-Lan; Van de Kooj, Bert; Kong, Yi Wen; Bandopadhayay, Pratiti; Beroukhim, Rameen; Sarkaria, Jann; Hammond, Paula; Yaffe, Michael
Abstract: Small molecule inhibitors targeting the BET bromodomain-containing protein BRD4 (BET inhibitors) are in early phase clinical develop for the treatment of several types of cancers, including CNS tumors. Studies have shed increasing insight into their anti-cancer mechanisms of action outside of its classical role in transcriptional downregulation of Myc . We recently reported additive effects between BET inhibitors and temozolomide in increasing DNA damage, tumor cell killing, and prolonging survival in intracranial mouse models of glioma. We now report that BET inhibition synergizes with PARP inhibition in an intracranial D458 patient-derived xenograft (PDX) model of type III medulloblastoma. Using a novel in-house cellular dual fluorescent reporter system of double-strand break repair called "DSB Spectrum" that detects a cell's ability to repair by non-homologous end-joining (NHEJ) or homologous recombination (HR), we show that treatment of D458 cells with the BET inhibitor OTX-015 causes DNA damage and DSB formation but the inability to repair via NHEJ or HR due to transcriptional downregulation of key repair pathway proteins. This induced HR-deficiency synergizes cells to PARP inhibition and decreases tumor burden and prolongs survival in vivo. Mechanistically, BET inhibition causes replication stress-induced DNA damage by increasing collisions between the transcription and replication machinery with failure to activate the replication stress DNA damage checkpoint. Co-incidentally, this allows for further leveraging of BET inhibitors with PARP inhibitors and other DNA damaging agents at much lower doses in combination that avoids systemic toxicity, potently decreases tumor burden, and significantly increases survival in PDX models of medulloblastoma and glioblastoma. Taken together, our results suggest a novel role for BRD4 as a master regulator of the DNA damage response in cells that allows for the discovery of novel higher order synergistic drug combinations with enhanced safety profiles and translational potential.